(untitled) (VERUM: Journal of Scientific Initiation, 2025)
This article analyzes transversality in history teaching as a pedagogical strategy aimed at the critical formation of students, breaking with the fragmentation of knowledge and articulating content with socially relevant themes, connecting past and present. The objective is to build debates to challenge political structures, the devaluation of the Humanities, and the precariousness of teaching work. The study highlights transversality as an instrument of resistance, favoring the valorization of historical and social experiences of historically silenced subjects, as a conquest of the struggles in defense of the democratization of education in Brazil. Based on a bibliographic review and the analysis of normative documents, the work reaffirms the centrality of history teaching in the formation of critical and reflective subjects, emphasizing the teacher’s role in mediating knowledge aimed at social transformation and democratic principles.